Vegetation gradients in Southern Cape mountains - Bond, William J (University of Cape Town, 2015)
Southern Cape Mountain fynbos has been little studied in the past so that management and planners have had to draw heavily on Western Cape experience. This study arose from the need to define local vegetation patterns and their interdependence with animal life, climate and soil as a necessary prerequisite to vegetation mapping and Fynbos is part of the diverse and complex Cape Floral Kingdom. Field taxonomy in fynbos is often problematic for trained botanists and is an overwhelming obstacle for mapping and monitoring of vegetation by untrained observers. Even the most unsophisticated observer, however, can recognize consistent variation in non-floristic characters such as vegetation height, density and the relative abundance of Proteaceae, small leaved shrubs and graminoid plants. A major aim of the study was thus to test the feasibility of deriving a non-floristic vegetation classification using easily learnt characters which had predictive value and was independent of the complication of high species turnover from one area to the next.